Enhancing Public Service Quality through Information Systems: A Case Study of PD Pontren in Sleman's Ministry of Religious Affairs - Uzma Qatrunnada, Almas (Journal of Islamic Education Management Research, 2023)
Purpose – This study explores the implementation of a public service information system through the PD Pontren Section at the Ministry of Religious Affairs in Sleman, focusing on the quality and effectiveness of services provided to the community. Design/methods/approach – Employing a qualitative, descriptive case study approach, the research utilized observations, semi-structured interviews, and a literature review. The data collection and analysis involved a three-step process: data reduction, data display, and data verification, enhancing reliability through triangulation. Findings – The implementation of the Integrated Service Unit (PTSP) by PD Pontren demonstrates an efficient and comprehensive approach to public service. This includes a unified service delivery process, adherence to five critical work cultures, and a focus on Diniyah and Islamic Boarding School education. The study identified significant improvements in service transparency, accessibility, and accountability. Research implications/limitations – While offering insights into effective public service systems, the study's focus on a single district limits its broader applicability. Comparative research across different contexts is recommended. Practical implications – The findings can inform policy formulation and administrative practices in educational settings, highlighting the role of integrated information systems in enhancing service quality. Originality/value – This research contributes to the understanding of the impact of information systems on public service delivery and educational quality, offering a model for other districts and educational institutions.